ANALISIS PENGARUH MENONTON TAYANGAN UTTARAN DI ANTEVE TERHADAP PERILAKU SOSIAL IBU RUMAH TANGGA - R. Rama Adhypoetra; Yos Horta Meliala (Jurnal Pustaka Komunikasi, 2018)
ANTV television station is one of the television has a flagship program that became the current phenomenon is the Indian series "Uttaran" which aired every day. This show is not only interested in teenagers but also among housewives. This research uses quantitative approach with the aim to know whether there is influence between watching impression Uttaran in ANTV to social behavior of housewife in RT 05 RW 08 Keluarahan Malaka Sari Kecamatan Duren Sawit, Jakarta Timur. The research technique used in this research is survey and technical data analysis that is tested simple regression that begins with univariate analysis for descriptive statistic and then proceed with bivariate analysis of pearson correlations. The results of this study also shows that watching uttaran impressions affect the social behavior of housewives, so H0 is rejected means that the variables watching the uttaran impressive effect positive and significan on the social behavior of housewife variables. This research needs to be examined from the side of men who notebene they can only give comments made by mothers.